Alternative Conduits for Microvascular Anastomoses. (June 2014) - Pontini, Alex; Tocco, Ilaria; Pandis, Laura; Bassetto, Franco; Vindigni, Vincenzo
Thrombotic events in vascular substitutes are the main cause of obliteration of most microvascular prostheses and subsequent failure of microvascular anastomoses. The development of new biomaterials for vascular replacement aims to obtain an ideal graft for microvascular surgery. Completely bioresorbable vascular prostheses with the capacity to induce regeneration and growth of a new vascular segment seem to overcome the limitations of contemporary artificial prostheses, mostly made of artificial materials and lacking the capacity to grow and be remodeled. Autologous vessels are currently the most used material for small-diameter arterial replacement. Immune acceptance is a major advantage offered by this technique, but the time required is a limitation in emergency surgery. The need for a prosthetic graft that would have the same properties as a small-diameter conduit has led investigators to pursue many avenues in vascular biology. This article details the development of microvascular synthetic prostheses, clarifying the current status and the future aims.